Building the Collective: Theories of the Archaic in Socialist Modernism, Romania circa 1958. Issue 1 (2nd January 2017) - Maxim, Juliana
Abstract : This essay looks at the seeming contradiction that existed in socialist Romania circa 1958 between certain primitivist tropes and an agenda of modernization in the discourse about socialist architecture. The search for archaic principles in both material and social form occurred in a variety of mediums and institutions, and the essay details two examples: the open-air collection of rural architecture of the Village Museum in Bucharest and the revival of the notion of the primitive commune in H. H. Stahl's ethnohistorical writings. The essay shows how the determinedly modernist architecture of the new socialist housing districts and, more generally, visual representations of the country's industrialization should be understood in this context of primitivist thinking. The essay argues that rapid socialist modernization was accompanied by an equally intense search for collective, unalienated practices thought to have existed inherently in the primitive.